Approaches to Effective Use of Human Resources in Public Service - SADYKOVA, Kuralay K.; KULZHAMBEKOVA, Alma E.; ABILMAZHINOV, Timur T.; KOKSHAROVA, Vera V. (Journal of Advanced Research in Law and Economics, 2017)
The research aims at performance assessment of human resource usage in public service as in the case of the Republic of Kazakhstan. The authors made their main emphasis on the methodological problem of public servants’ performance assessment. The paper includes an analysis of the assessment methodology for human resource management and presents systemic problems that prevent establishment of a professional community of civil servants. The discussed problems are associated with a movement of staff, their career development, and a staffing level in government bodies. In the research, the authors reviewed findings from the questionnaire survey of public servants. They, too, collected in-house performance assessment forms for such public servants. The authors suggested an algorithm to make decisions of methods helpful to evaluate performance in staff development programs. The findings might be useful for public authorities to develop government programs and strategies in HR management.